2016
DOI: 10.1007/s13143-015-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloud — Aerosol interaction during lightning activity over land and ocean: Precipitation pattern assessment

Abstract: The present study attempts to identify the land -ocean contrast in cloud -aerosol relation during lightning and non-lightning days and its effect on subsequent precipitation pattern. The thermal hypothesis in view of Convective Available Potential Energy (CAPE) behind the land -ocean contrast is observed to be insignificant in the present study region. The result shows that the lightning activities are significantly and positively correlated with aerosols over both land and ocean in case of low aerosol loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Since their measurements were taken before the onset of convection, it seems reasonable to assume that aerosols emitted earlier in the day or at night remained within the atmosphere to influence convection later that morning or afternoon. The results were also consistent with those of Pal et al (2016), who found that lightning activities were significantly and positively correlated with aerosols over both land and ocean in case of low aerosol loading, while for high aerosol loading the correlation was significant only over land.…”
Section: Discussionsupporting
confidence: 92%
“…Since their measurements were taken before the onset of convection, it seems reasonable to assume that aerosols emitted earlier in the day or at night remained within the atmosphere to influence convection later that morning or afternoon. The results were also consistent with those of Pal et al (2016), who found that lightning activities were significantly and positively correlated with aerosols over both land and ocean in case of low aerosol loading, while for high aerosol loading the correlation was significant only over land.…”
Section: Discussionsupporting
confidence: 92%
“…The increased aerosol loading during pre-monsoon was found to be a combined effect of agricultural waste burning activity, forest fire, anthropogenic emission, and long-range transport, as well containing dessert soil/dust, organic matter, gaseous product (sulfate and nitrate), and soot particles [61]. A previous study has reported a similar pattern of increased lightning flash density over the land area of the Indian subcontinent during pre-monsoon months, with a peak in June, and the study also reported an increase in aerosol in July through external inflow and a sudden decrease in the subsequent months, possibly due to the monsoon precipitation [62]. The monthly climatology of LFRD with AOD is represented in Figure 11 and shows that the aerosol concentration tends to increase from March and reaches its maximum in July.…”
Section: Lightning and Aerosolsmentioning
confidence: 60%
“…Some colleges even think that public English courses have no practical use so that more teaching content cannot give play to the actual effect, and students can only learn passively. Reference [19] research shows that colleges and universities adopt the hierarchical teaching mode, but the effect is very little, just to meet the needs of teaching. They are indifferent to students' interests and future prospects.…”
Section: Related Workmentioning
confidence: 99%